Study on Optical Fiber Insertion in Underground Telecommunication Networks Using Hydraulic Similarity. (2016) - Grigoriu, Mircea; Popescu, Marius Constantin
Abstract: The European regulations require a new approach of cities facilities networks, including the communication ones. In this respect, the communication providers generalize the underground networks, following the streets trails. The transmission support consists in a network of tubes, protecting a number of micro-tubes/microducts, which protect the real transmission facilitators made by optical fibers. Presently, the producers of this type of devices promote special norms of information on characteristics and installation of the product, but there are not reliable accepted standardized methods for optical fibers insertion in pre-installed micro-tubes/microducts and for the devices forces computation, necessary for underground communication networks. The micro-tubes are already installed in the protection cables and together are buried in the ground on different routes. It appears the necessity to introduce the fibers in the micro-tubes in this situation. Generally, it is a significant difference between the practical reality and the producers norms and indicators. In order to explain this situation, and considering the optical fibers dimensions, and the necessity to insert the fibers using specific lubricants, the paper propose a similarity model of the optical fibers insertion in the micro-tubes with the hydraulic model of laminar incompressible fluids flow in parallel or concentric micro- layers. In this phase, there are presented the results of experimental measurements and tests on in situ networks, composed by different types of materials and lubricants, as support for the hydraulic similitude.